Knowledge Management: An Information Technology Prospective - Gulati, Anjali (DESIDOC Journal of Library & Information Technology, 2003)
Knowledge management describes the way in which organisations are attempting to capture, enhance, and use the knowledge necessary for their survival. In this paper, the author discusses about concept of knowledge management, contribution of information technology in enabling its initiatives which have their aim of achieving the competitive advantage for both the organisation and its employees. The information-based paradigm shift now-a-days is the result of the effective application of information technology to knowledge resources. Further, the paper highlights .transformational role of knowledge manager from 'Information keeper' to 'knowledge smith'. Finally, the paper reflects knowledge management issues, which include developing, implementing and maintaining the appropriate technical and organisational infrastructure to enable knowledge sharing, developing information technology skills in the staff and overcoming information overload. http://dx.doi.org/10.14429/dbit.19.6.3501